2007
DOI: 10.1111/j.1365-246x.2007.03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Waveform modelling of teleseismicS, Sp, SsPmP, and shear-coupled PL waves for crust- and upper-mantle velocity structure beneath Africa

Abstract: S U M M A R YWe describe a waveform modelling technique and demonstrate its application to determine the crust-and upper-mantle velocity structure beneath Africa. Our technique uses a parallelized reflectivity method to compute synthetic seismograms and fits the observed waveforms by a global optimization technique based on a Very Fast Simulated Annealing (VFSA). We match the S, Sp, SsPmP and shear-coupled PL phases in seismograms of deep (200-800 km), moderateto-large magnitude (5.5-7.0) earthquakes recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
(113 reference statements)
2
9
0
Order By: Relevance
“…The Figure 6a, demonstrating the significance of the peak which is marked by the black dot in Figure 6a. crustal thickness is similar to that obtained by Sandvol et al [1998] and Gangopadhyay et al [2007], and is almost identical to the value used by Ayadi et al [2000] in their tomographic inversion. The crustal P-wave velocity of 6.5 km/s is chosen based on active-source seismic surveys conducted in stable parts of Africa such as the Kaapvaal craton [Durrheim and Green, 1992] and the average crustal P-wave velocity from the RF studies of Sandvol et al [1998] and Gangopadhyay et al [2007].…”
Section: Overall Crustal Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…The Figure 6a, demonstrating the significance of the peak which is marked by the black dot in Figure 6a. crustal thickness is similar to that obtained by Sandvol et al [1998] and Gangopadhyay et al [2007], and is almost identical to the value used by Ayadi et al [2000] in their tomographic inversion. The crustal P-wave velocity of 6.5 km/s is chosen based on active-source seismic surveys conducted in stable parts of Africa such as the Kaapvaal craton [Durrheim and Green, 1992] and the average crustal P-wave velocity from the RF studies of Sandvol et al [1998] and Gangopadhyay et al [2007].…”
Section: Overall Crustal Propertiessupporting
confidence: 85%
“…Sandvol et al [1998] concluded that the crustal structure beneath the station is very homogeneous. Similarly, under the assumption of a laterally homogeneous crust, Gangopadhyay et al [2007] revealed a crustal thickness of 36 km and a P-and S-wave velocity range of 6.25-6.8 km/s and 3.1-3.9 km/s, respectively, using data from 6 events. As shown below, our results suggest a dramatic contrast in Moho characteristics between the Tefedest and Laouni terranes sampled by the 1386 events used in the study, highlighting the importance of additional data and that of a data analysis approach that is beyond the common assumption of laterally homogeneous crust beneath a station.…”
Section: Results Of Previous Geophysical Studiesmentioning
confidence: 99%
“…Linear methods, such as least squares methods, are best suited to finding models that are quite similar to the starting model, rather than the single, best fitting model within a given model space. Therefore, in this analysis, we employ a stochastic, nonlinear, global optimization technique known as Very Fast Simulated Annealing (VFSA), which is weakly dependent on the choice of initial model [ Sen and Stoffa , ; Gangopadhyay et al ., ; Agrawal et al ., ; Zhao et al ., ; Ingber , ]. VFSA is a variant of Simulated Annealing (SA) that is aimed at making computations more efficient [ Ingber , ; Sen and Stoffa , ].…”
Section: Methodsmentioning
confidence: 99%
“…Monte Carlo technique) to address this problem. Many authors have previously described the use of this method in waveform inversion, such as simulated annealing (Sen & Stoffa 1991; Riepl et al 1995; Steck 1995; Zhao et al 1996; Gangopadhyay et al . 2007), the genetic algorithm (Noves et al 1996; Shibutani et al 1996; Bhattacharyya et al 1999; Chang & Baag 2006; Li et al 2007; Lee & Baag 2008) and the neighbourhood algorithm (Sambridge 1999a,b; Yoshizawa & Kennett 2002).…”
Section: Introductionmentioning
confidence: 99%